Agro-residues and weed biomass as a source bioenergy: Implications for sustainable management and valorization of low-value biowastes - Deb, Utsab; Bhuyan, Nilutpal; Bhattacharya, Satya Sundar; Kataki, Rupam (International Journal of Renewable Energy Development, 2019)
Biomass resources are gaining increasing importance world over due to their ease of conversion to various energy product in the face of depleting fossil fuel store and increasing environmental concerns over their use. The present work elucidates different physico-chemical properties of three biomasses, paddy straw (PS)- an agricultural residue, spent paddy straw obtained after mushroom cultivation (SS), and a noxious weed (Parthenium hysterophorus; PR) to understand their properties and to explore the feasibility of using them as feedstocks in different biomass to bioenergy conversion routes. In addition to physico-chemical analysis, biochemical analysis of these biomasses along with XRD, thermogravimetric analysis, FTIR and SEM analysis have been carried out. Present study suggests that PS is a better choice as feedstock compared to both PR and SS. The calorific value to ash content ratio is more in PS (1.13) as compared to PR (1.06) and SS (0.84). Thus, it may be inferred that the biomasses in question are at par with commonly used bio-energy feedstocks like sugarcane bagasse and corn cob. Â©2019. CBIORE-IJRED. All rights reserved